Implementation of the Religious Moderation Policy Regarding Religious Learning in Tanjungpinang City State High Schools : Implementasi Kebijakan Moderasi Beragama Tentang Pembelajaran Agama Di Sekolah Lanjutan Tingkat Atas Negeri Kota Tanjungpinang - Hironimus Betuwoa; Rudi Subiyakto; Okparizan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Implementation is a concept that attempts to look at a number of key factors that influence policy implementation. The implementation of religious moderation policies in Indonesia, especially in Tanjungpinang City, has not been and is not even optimal. This phenomenon is interesting by looking at the root of the problem. This research uses descriptive research methods with a qualitative approach. Researchers used two data collection techniques, namely: a) Literature Study, Concentrating on collecting data through library data collection techniques, analyzing research materials from books and scientific journals, newspapers and articles in general. Library data can be accessed by purchasing books related to research, accessing offline or online libraries such as the digital library application of the National Library of the Republic of Indonesia (iPusnas). b) Documentation Studies, namely collecting data from a number of official documents. These official documents include data, press statements and reports from state high school schools in Tanjungpinang, the Riau Islands Provincial Education Office, the Tanjungpinang Catholic Church. The primary data collection technique is through interviewing the views of source participants regarding the problems felt by the participants. The research results show that the case study at the Tanjungpinang State High School occurred for several reasons, including: the absence of Catholic Religious Educators with PNS or PPPK status; the number of students who are Catholic does not meet the quota in terms of numbers; and there are no places or classrooms provided for Catholic religious learning activities. The Tanjungpinang Catholic Church took a solution with educational steps in the form of gathering Catholic children who attend high school level state schools in Tanjungpinang City and looking for volunteer teachers to provide Catholic religious lessons and then provide grades to the school.